Spatial and temporal distributions of macrobenthic communities and their environmental driving factors in deepwater reservoirs: a case study of Yinghu Lake, China - Chen, Ruoyu; Hu, Fangzheng; Wang, Xinyu; Lin, Haibin; Ye, Zhangyi; Hu, Zhongjun; Liu, Qigen (Frontiers in Ecology and Evolution, 2025)
The characteristics of macrobenthic community structure can accurately indicate the ecological health of aquatic environments. To elucidate the spatiotemporal responses of macrobenthic communities and environmental factors in reservoirs, this study investigated macrobenthos and environmental parameters in Yinghu Lake during spring (May), summer (August), and autumn (November). The results showed that the trophic level index (TLI), total nitrogen (TN) and total phosphorus (TP) were significantly higher and pH was significantly lower (P < 0.05) at the developed sites (DS) than at the undeveloped sites (UDS). The survey identified 32 macrobenthos species representing 3 phylums and 5 orders. PERMANOVA analyses showed that the macrobenthic community structure of Yinghu Lake differed significantly between regions, Limnodrilus hoffmeisteri from the gathering collectors (20.47%) and Corbicula fluminea from the filtering collectors (7.82%) were the primary species driving the differences. The results of the two-way ANOVA indicated that species richness, the Margalef index (D), and the functional feeding group Margalef index (FFG-D) were significantly lower in summer than in autumn (P < 0.05). FFG-D was also significantly lower at the DS compared to the UDS (P < 0.05), while the interaction effects of season and region on these indicators were not significant (P > 0.05). Redundancy analysis (RDA) and generalized additive modelling (GAM) indicated that the permanganate index (CODMn) and total dissolved solids altered the macrobenthic community structure towards oligochaete and gathering collectors-dominated assemblages. Moreover, macrobenthic diversity was constrained by high total dissolved solids concentrations, sediment organic carbon (OC_s), soluble reactive phosphorus (SRP), low sediment total phosphorus (TP_s), high water temperature, and deep water. In summary, the spatiotemporal variations in water quality and macrobenthos communities in the reservoir were influenced by natural conditions and anthropogenic disturbances. This study provides valuable insights into the spatiotemporal dynamics of macrobenthic communities and contributes to a more comprehensive understanding of the role of biodiversity in maintaining the stability of large reservoir ecosystems.